ByzRev 05.2023.021: Nikos Zagklas, Theodoros Prodromos: Miscellaneous Poems.: An Edition and Literary Study (Oxford Studies in Byzantium). : Oxford: Oxford University Press 2023. - Zaripov, Yan (The Byzantine Review, 2023)
Nikos Zagklas, Theodoros Prodromos: Miscellaneous Poems. An Edition and Literary Study (Oxford Studies in Byzantium). Oxford: Oxford University Press 2023. XVI, 382 pp. – ISBN 978-0-19-288692-7